Multi-level characteristics of TiOx transparent non-volatile resistive switching device by embedding SiO2 nanoparticles - Sera Kwon (Nature Portfolio, 2021)
Abstract TiOx-based resistive switching devices have recently attracted attention as a promising candidate for next-generation non-volatile memory devices. A number of studies have attempted to increase the structural density of resistive switching devices. The fabrication of a multi-level switching device is a feasible method for increasing the density of the memory cell. Herein, we attempt to obtain a non-volatile multi-level switching memory device that is highly transparent by embedding SiO2 nanoparticles (NPs) into the TiOx matrix (TiOx@SiO2 NPs). The fully transparent resistive switching device is fabricated with an ITO/TiOx@SiO2 NPs/ITO structure on glass substrate, and it shows transmittance over 95% in the visible range. The TiOx@SiO2 NPs device shows outstanding switching characteristics, such as a high on/off ratio, long retention time, good endurance, and distinguishable multi-level switching. To understand multi-level switching characteristics by adjusting the set voltages, we analyze the switching mechanism in each resistive state. This method represents a promising approach for high-performance non-volatile multi-level memory applications.